Molecular and cytogenetic dissection of stripe rust resistance gene Yr83 from rye 6R and generation of resistant germplasm in wheat breeding - Li, Guangrong; Li, Jianbo; Zhang, Yao; Ma, Qiang; Yang, Ennian; Zhang, Peng; Dundas, Ian; Yang, Zujun (Frontiers in Plant Science, 2022)
Stripe rust resistance gene Yr83 derived from chromosome 6R of rye (Secale cereale) “Merced” has displayed high resistance to both Australian and Chinese wheat stripe rust isolates. With the aim to physically map Yr83 to a more precise region, new wheat- 6R deletion and translocation lines were produced from derived progenies of the 6R(6D) substitution line. The non-denaturing fluorescence in situ hybridization (ND-FISH) patterns of 6R were established to precisely characterize the variations of 6R in different wheat backgrounds. Comparative ND-FISH analysis localized the breakpoints of 6RL chromosomes relative to Oligo-pSc200 and Oligo-pSc119.2 rich sites in deletion lines. Molecular marker and resistance analysis confirmed that Yr83 is physically located at the fraction length (FL) 0.87-1.00 of 6RL and covers the corresponding region of 806-881 Mb in the reference genome sequence of Lo7. Oligo-FISH painting demonstrated that the region carrying Yr83 was syntenic to the distal end of long arm of homoeologous group 7 of the Triticeae genome. The developed wheat-6R lines carrying the Yr83 gene will be useful for breeding for rust resistance.